Debate: Use of the Term ‘Bonded Labour’ is a Must in the Context of India - Prasad, Kiran Kamal (Anti-Trafficking Review, 2015)
There is no question that we should distinguish between forced labour, trafficking and slavery. But, we should also include in the debate another concept, ‘bonded labour,’ as it describes a distinct and widespread form of forced labour in India that does not fully accord with the International Labour Organization’s (ILO) definition of forced labour. The sociopolitical reality in India and bonded labour’s intimate link with the Indian caste system demand that the term ‘bonded labour’ be retained in the discourse on forced labour and trafficking in persons. Addressing bonded labour enables two interconnected areas of exploitation and discrimination to be addressed, namely working towards emancipation of the minority Dalit community and of the Moolnivasi indigenous communities.